The global etiquette guide to Asia - Foster, Dean Allen (Wiley, 2000)
Includes index.; pt. 1. The Pacific Rim : It's not what you say, but how you say it. The East Asian cultures : Japan -- The East Asian cultures : China, Hong Kong, and Taiwan -- The East Asian cultures : South Korea -- The Southeast Asian cultures : Thailand -- The Southeast Asian cultures : Indonesia -- The Southeast Asian cultures : The Philippines -- The Southeast Asian cultures : Malaysia and Singapore -- The Southeast Asian cultures of Indochina : Vietnam, Laos, Cambodia, and Myanmar (Burma) -- The Australasian cultures : Australia and New Zealand -- pt. 2. South Asia, Central Asia, and Eurasia intense incense. The South Asian cultures : India -- The South Asian cultures : Pakistan and Bangladesh -- The South Asian cultures : Sri Lanka and the Himalayan Kingdoms -- The Central Asian cultures : Kazakhstan, Uzbekistan, Turkmenistan, Tajilistan, Kyrgyzstan, and Afghanistan -- The Eurasian cultures : Turkey and the Caucasus -- pt. 3. Southwest Asia and the Asian Arab world holiness and humility. The Gulf Arab cultures : Saudi Arabia -- The Gulf Arab cultures : The gulf coastal state of Kuwait, Oman, Qatar, Bahrain, United Arab Emirates, and Yemen -- The Arab Levantine cultures : Lebanon, Syria, and Jordan -- The Judaic Levantine cultures : Israel.; "Just as customs vary greatly between Asia and the West, so do they vary among the diverse nations of Asia. What is proper and expected in Malaysia, for example, may be a deal-breaker in India. The Global Etiquette Guide to Asia will familiarize you with the customs, habits, tastes, and mores of every key Asian nation - over forty in all - and help you guarantee the mutual respect and acceptance that are vital for keeping every international business relationship agreeable, effective, and successful."--Jacket.